Time and dose relationships between schisandrin B- and schisandrae fructus oil-induced hepatotoxicity and the associated elevations in hepatic and serum triglyceride levels in mice - Zhang, Yi (Dove Medical Press, 2014)
BACKGROUND: Schisandrin B (Sch B), a dibenzocyclooctadiene compound, is isolated from schisandrae fructus (SF). This study was conducted to compare the time- and dose-response between Sch B- and SF oil (SFO)-induced changes in hepatic and serum parameters in mice. METHODS: Institute of Cancer Research (ICR) mice were given a single oral dose of Sch B (0.125–2 g/kg) or SFO (0.3–5 g/kg). Serum alanine aminotransferase (ALT) activity, hepatic malondialdehyde, and triglyceride (TG) levels were measured at increasing time intervals within 6–120 hours postdosing. RESULTS: Serum ALT activity was elevated by 60%, with maximum effect (E(max)) =45.77 U/L and affinity (K(D)) =1.25 g/kg at 48–96 hours following Sch B, but not SFO, treatment. Sch B and SFO treatments increased hepatic malondialdehyde level by 70% (E(max) =2.30 nmol/mg protein and K(D) =0.41 g/kg) and 22% (E(max) =1.42 nmol/mg protein and K(D) =2.56 g/kg) at 72 hours postdosing, respectively. Hepatic index was increased by 16%–60% (E(max) =11.01, K(D) =0.68 g/kg) and 8%–32% (E(max) =9.88, K(D) =4.47 g/kg) at 12–120 hours and 24–120 hours after the administration of Sch B and SFO, respectively. Hepatic TG level was increased by 40%–158% and 35%–85%, respectively, at 12–96 hours and 6–48 hours after Sch B and SFO treatment, respectively. The values of E(max) and K(D) for Sch B/SFO-induced increase in hepatic TG were estimated to be 22.94/15.02 μmol/g and 0.78/3.03 g/kg, respectively. Both Sch B and SFO increased serum TG (up to 427% and 123%, respectively), with the values of E(max) =5.50/4.60 mmol/L and K(D) =0.43/2.84 g/kg, respectively. CONCLUSION: The findings indicated that Sch B/SFO-induced increases in serum/hepatic parameters occurred in a time-dependent manner, with the time of onset being serum TG level < hepatic TG level < hepatic index < serum ALT activity. However, the time of recovery of these parameters to normal values varied as follow: serum TG level < hepatic TG level and liver injury < hepatic index. The E(max) and affinity of Sch B on tissue/enzyme/receptor were larger than those of SFO.